Percepção de liberdade no lazer: a experiência do lazer em adolescentes usuários de substâncias psicotrópicas - Almeida, Diego Eugenio Roquette Godoy [UNIFESP] (2014)
The increasing use / abuse of drugs among adolescents has become an urgent topic of understanding between sectors of society, caused by the impact on health. By the current advances of laws protecting adolescent, to assure them full protection through actions that make available to the development, leisure emerges as a fundamental element. Attaches itself to pleasure the possibility of rest, fun, psychosocial development and strengthening social support network, although traditionally associated with leisure is "bad social habits." Many leisure facilities were modeled by the idea of hygiene and control or even little investment by the various social sectors in this field. In this study, leisure is understood beyond the work - leisure dichotomy translated into "free time" work. The experience of leisure activity can occur at any time or, provided there is perceived freedom during the occupation and intrinsic motivation. Leisure as attitude includes the perception of competence, control, need, depth and involvement in leisure experiences. OBJECTIVES: To systematically review the major databases in health association or effect of leisure on the use of substances; verify that substance use among adolescents 14-18 years is related to perceptions of freedom in leisure. METHODS: A pre-test with 66 teenagers as a way to ensure the intelligibility was performed. Was selected for convenience at Projeto Quixote 186 adolescents in a school in Guarulhos . It used as instruments Questionnaire Data Sociodemographic and Leisure (QSDL) to define the profile of the sample, The Leisure Diagnostic Battery, version B (PLL) to measure Perceived Freedom in Leisure and Drug Use Screening Inventory (DUSI) for classification of substance use, all self-administered. The data underwent descriptive analysis with the measures of central tendency and dispersion. To analyze the effect we used the ANOVA test, comparison of means, independent t test, interdependence of categorical variables, chi-square, prediction, linear regression. The main independent variables were type of substance used, frequency and quantity of use. The accepted level of significance for all the results was 5%. RESULTS: 165 reviews were analyzed . The frequency of use of ecstasy and marijuana in the last month were related to higher rates of PLL (p ≤ .05). The number of substances used in the last month had no significant effect. It was also observed that the predictive ability of the elements of the PLL to the risk of use was low. The nature of leisure activities were not associated with use. CONCLUSION: The study suggests specific components of leisure related to the frequency of substance use, such as perceived control and need at leisure. Although not statistically significant, there was a trend to increased perception of freedom as the increased use of substances.